1964
DOI: 10.1002/app.1964.070080416
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of a neophyl type anion exchange resin

Abstract: The common strongly basic Type I anion exchange resins, magnified image contain benzylictrimethylammonium groups. In OH− form, the resins are unstable above 60°C. due to nucleophilic attack by OH− on the benzylic and methyl carbon atoms. Reactivity of benzylic carbon sites relative to methyl sites is about 4 to 1. More stable resins would be desirable, so laboratory synthesis and stability study was made of a resin which contained neither benzylic carbon atoms nor β‐carbon atoms having hydrogen atoms which cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…This is consistent with the conclusion that the benzyl S N 2 pathway is the dominant degradation pathway for unsubstituted BTMA + . 18,20,26,27 For the double-meta −OCH 3 substitution, the benzyl S N 1 G = is 136.4 kJ/mol, close to the value of the unsubstituted BTMA + . For the double-meta −N(CH 3 ) 2 substitution, the benzyl S N 1 G = is 115.9 kJ/mol, still larger than its benzyl S N 2 G = (104.2 kJ/mol), although the gap between S N 1 G = and S N 2 G = is much smaller.…”
Section: Multivalentmentioning
confidence: 61%
“…This is consistent with the conclusion that the benzyl S N 2 pathway is the dominant degradation pathway for unsubstituted BTMA + . 18,20,26,27 For the double-meta −OCH 3 substitution, the benzyl S N 1 G = is 136.4 kJ/mol, close to the value of the unsubstituted BTMA + . For the double-meta −N(CH 3 ) 2 substitution, the benzyl S N 1 G = is 115.9 kJ/mol, still larger than its benzyl S N 2 G = (104.2 kJ/mol), although the gap between S N 1 G = and S N 2 G = is much smaller.…”
Section: Multivalentmentioning
confidence: 61%
“…[4][5][6][7][8] Unfortunately, the replacement of the well-established proton exchange membranes (PEM) by AEMs in their hydroxide form (hydroxide exchange membrane: HEM) is hampered by several stability issues. [8,[11][12][13][14][15][16][17] Base-induced decomposition of QAs is also an issue with their use as cations in ionic liquids (ILs). Decomposition typically starts at temperatures above T = 60 8C and leads to a reduction of ion exchange capacity (IEC), conductivity, and mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition typically starts at temperatures above T = 60 8C and leads to a reduction of ion exchange capacity (IEC), conductivity, and mechanical strength. [8,[11][12][13][14][15][16][17] Base-induced decomposition of QAs is also an issue with their use as cations in ionic liquids (ILs). While ILs are generally stable under reducing and oxidizing conditions, their low base stability [18] is preventing them from being used as solvent for base-catalyzed reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The suspension copolymerization of v-bromoalkylstyrenes or v-bromoalkoxymethylstyrenes with DVB at 70ЊC could afford crosslinked poly( v-bro- atoms, which results in the decreased strong base capacity (see Scheme 4). [5][6][7] The main reaction in this decomposition is the styrene) in good yields (ú90%). The microporous former one, which liberates the free trimethylam-(gel-type) polymer beads were treated with triine base.…”
Section: Preparation Of Anion Exchange Resinsmentioning
confidence: 99%
“…We have already reported that spacer-modified, ide form or basic conditions and are not suitable polymer-supported phosphonium salt catalysts for applications at temperatures above 60ЊC. [5][6][7] such as (II) have higher chemical stability than The low thermal stability of the exchangers of the do conventional polymer-supported phosphonium salt catalysts such as (III), which contain a benzylic onium structure in reactions of alkyl halides cm 01 ( C{Br ) . NMR ( CDCl 3 ) : d 1.64 -1.74 ( m, 2H, OCH 2 C H 2 CH 2 CH 2 Br ) ; 1.85 -1.96 ( m, 2H, OCH 2 CH 2 C H 2 CH 2 Br ) ; 3.33 -3.45 ( m, 4H, OC H 2 CH 2 CH 2 C H 2 Br ) ; 4.42 ( s, 2H, PhCH 2 ) ; 5.17-5.23 (m, 1H, trans CH 2 |); 5.67-5.78 (m, Therefore, the introduction of spacer chains be-1H, cisCH 2 |); 6.61-6.73 (m, 1H, CH|); 7.15tween the benzene ring and the quaternary nitro-7.36 (m, 4H, phenylene).…”
Section: Introductionmentioning
confidence: 99%